Role of Copper Migration in Nanoscale Ageing of Supported CuO/Al2O3 in Redox Conditions: A Combined Multiscale X‐ray and Electron Microscopy Study. Issue 4 (24th January 2023) - Sharna, Sharmin; Rouchon, Virgile; Legens, Christèle; Taleb, Anne‐Lise; Stanescu, Stefan; Bouillet, Corinne; Lambert, Arnold; Briois, Valerie; Chiche, David; Gay, Anne‐Sophie; Ersen, Ovidiu
Abstract: Chemical Looping Combustion is a promising midterm solution to mitigate CO2 emission, by carrying out indirect fuel combustion and allowing inherent separation of CO2 . During the CLC process, an oxygen carrying material is subjected to successive oxidation‐reduction reactions at high temperature which induce significant material degradation. CuO/Al2 O3 based materials have been widely considered as promising oxygen carriers (OC). However, the oxygen carrier ageing mechanisms (active phase migration and interactions with the support, phase transitions) are not well understood. Herein, an in‐depth overview of the material evolution is achieved by employing a multi‐scale characterization approach. At the μm‐scale, copper migration within the alumina support has been observed using Scanning Transmission X‐ray Microscopy (STXM) and Scanning Electron Microscopy (SEM). The spatial distribution of the Cu−Al species provides information on copper mobility and the different phases interactions. A comprehensive mechanism is proposed concerning the redox behaviour of the CuO/Al2 O3 system, relating the diffusion of the Cu‐species, the active phase‐support interactions, and the role of copper in the Al2 O3 support phase transition to the temperature and the number of redox cycles. Understanding the ageing process of CuO/Al2 O3 materials paves a way to design more stable oxygen‐carriers. Abstract : Multi ‐Scale Imaging Techniques to Design Stable Oxygen Carriers : CuO/Al2 O3 is a promising material for indirect combustion with inherent CO2 capture process owing to its high oxygen carrying capacity. In this paper, we report the ageing mechanism of the material at the nano‐micrometric scale as a function of successive oxidation‐reduction reactions.